The Effect of Using the Reciprocal Teaching and Training Methods on Some Elements of Physical Fitness Among Female Physical Education Students at Palestine Technical University - Alhayja, Fatema Abu; Maddeh, Talel; Souid, Ines; Budaier, Awad Qasim; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
The current study aimed to identify the effect of using the reciprocal and training methods of teaching on some elements of physical fitness among female physical education students at Palestine Technical University. In order to achieve the objectives of the study, three physical tests were applied. The study used the experimental approach to measure the level of some Elements of physical fitness (speed, muscular strength, and flexibility) according to the teaching method used. The study sample consisted of all (40) fourth-year female students in the Department of Physical Education at Kadoorie University in the first semester of the academic year 2021/2022. The results of the study showed that the students who studied by the reciprocal method obtained the lowest arithmetic mean (5.77 seconds) in the dimensional measurements of speed. This indicates that it is the most effective method in improving the runner’s speed, followed by the students who studied the training method with an arithmetic mean of (6.14). As well as the same arrangement in the post-measurement of flexibility, where the average flexibility of the students who studied by the reciprocal method was (38.20). In light of theses results, a set of recommendations were put forward, the most prominent of which is that teaching methods in physical education have the highest probability of positively affecting a large number of female students. It is necessary to diversify the use of teaching methods in Physical education classes due to the specificity of each teaching method in the development of physical activity.